PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KANTOR PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PAREPARE - Almukarram, Ersya Graha (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of motivation and work discipline on the performance of PDAM Parepare City employees. This research method is quantitative descriptive research. The research was conducted by collecting information from a sample by asking through a questionnaire or interview. Based on the data obtained from the analysis, the following conclusions can be drawn. Based on the calculation results, it is obtained that t-count is 3,590 > t-table is 1,299 (3,590 > 1,299) then the hypothesis is accepted, meaning that work motivation has a positive effect on employee performance. then employee performance also decreases with an error rate of 5% and Based on the calculation results obtained t-count of 2,316 > t-table of 1,299 (2,316 > 1,299) then the hypothesis is accepted meaning that work discipline has a positive effect on employee performance if the independent variable, namely works discipline increases, performance employees also increase and vice versa if the independent variable, namely works discipline decreases, employee performance also decreases with an error rate of 5%.